(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
Khadi- the original fabric of India is alternatively termed as “Khaddar”, a hand-spun and hand woven material, greatly helps to sustain the rural economy by providing employment to rural artisans and women. People who wear Khadi are self-motivated and bore a positive attitude to buy the fabric as indicated through the application of Theory of Planned Behaviour in the study. The contribution of Designers is immense to attract potential buyers for wearing Khadi. Despite being the culture and heritage, Khadi is not worn by the masses. Therefore in this paper an attempt has been made to find out the reasons for the non-acceptance of Khadi and promote it as a fashion fabric through the survey. Young Celebrity endorsement, Online Sales, promoting exports, Production research for quality improvement and round-the-year discount seasons have been suggested to make Khadi a long-lived sustainable fabric.